Clinical and immunological efficacy of interferonotherapy in rotavirus infection in infants - A. N. Os'kin; S. G. Gorbunov; L. N. Mazankova; S. A. Lugovskaya; E. V. Naumova; M. E. Pochtar' (Журнал инфектологии)
Purpose: to improve the complex therapy of rotavirus infection in infants by including interferon and to evaluate its clinical and immunological effectiveness.Materials and methods. Infants without infectious pathology and with rotavirus infection, who were on standard therapy and treatment, including standard therapy and interferon (20 in each group), were examined using general clinical methods. The diagnosis of rotavirus infection was carried out by molecular-genetic method and immunochromatography. Indicators of cellular immunity were determined by flow cytometry. Statistical processing of the results was carried out using the STATISTICA 8.0 program for related and independent samples using the nonparametric Mann-Whitney test and χ2.Summary. In all infants with rotavirus infection, the disease occurred in a moderate form with symptoms of grade II exicosis. In the group of patients who received an additional interferon drug as part of complex therapy, the duration of intoxication symptoms was significantly less, and in the hemogram at discharge from the hospital, the relative content of neutrophils was higher and monocytes lower compared to infants who were only on standard treatment, which corresponded to the norm. In the acute period of rotavirus infection, the relative level of lymphocytes decreased, and NK cells and T-NK cells increased compared to healthy infants. The relative number of cells expressing TLR-3 at the beginning of the disease was lower than in the control group. The inclusion of interferon in the complex therapy contributes to normalization of the relative number of NK cells, while maintaining an increased content of T-NK cells in both relative and absolute terms compared to healthy infants, and a reduced content of cells expressing TLR-3.Conclusion. Currently, rotavirus infection in infants is typical, the most pronounced and long-lasting clinical symptom of the disease is watery diarrhea. The use of interferon in complex therapy helps to reduce the duration of intoxication and normalize the hemogram. Changes in the immune status in the acute period of rotavirus infection indicate increased antigenic stimulation of the cell link and inhibition of the synthesis of pro-inflammatory cytokines, including interferons, under the influence of rotavirus, which is the justification for the use of interferon therapy.